2018
DOI: 10.25115/ejrep.v10i28.1537
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Self-Perceptions of Oral Narrative Competencies and Anxiety in the EFL Context

Abstract: Introduction. Due to a considerable lack in empirical efforts and appropriate instruments, and theo-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 115 publications
1
3
0
Order By: Relevance
“…This finding indicates the strong empirical overlap among the worry, avoidance, and emotionality responsesand, thus, the cognitivemotivational interplay of anxiety components. Similarly, close relations had been already found elsewhere (Deffenbacher, 1980;Hodapp & Benson, 1997;Cassady & Johnson, 2002;Chin, Williams, Taylor, & Harvey, 2017;Hong & Karstensson, 2002;Sarason, 1984), especially with respect to domain-or task-specific facets of test anxiety (Faber, 1995(Faber, , 2012b. By no means, this result does challenge the need for a separate assessment of worry, avoidance, and emotionality cognitions.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This finding indicates the strong empirical overlap among the worry, avoidance, and emotionality responsesand, thus, the cognitivemotivational interplay of anxiety components. Similarly, close relations had been already found elsewhere (Deffenbacher, 1980;Hodapp & Benson, 1997;Cassady & Johnson, 2002;Chin, Williams, Taylor, & Harvey, 2017;Hong & Karstensson, 2002;Sarason, 1984), especially with respect to domain-or task-specific facets of test anxiety (Faber, 1995(Faber, , 2012b. By no means, this result does challenge the need for a separate assessment of worry, avoidance, and emotionality cognitions.…”
Section: Discussionsupporting
confidence: 80%
“…However, relevant research findings in the test anxiety field had demonstrated these components being substantially correlated (Deffenbacher, 1980;Cassady & Johnson, 2002;Hodapp & Benson, 1997;Hong & Karstensson, 2002;Sarason, 1984). Furthermore, in certain research contexts dealing with school students' domainor subject-specific test anxieties, all worry, avoidance, and emotionally items repeatedly loaded on one common anxiety factor (Faber, 1995(Faber, , 2012b. Therefore, an accurate prediction of the scale's ultimate factor structure seemed difficult.…”
Section: Validation Framework and Objectivesmentioning
confidence: 99%
“…Additional support for this perspective comes from similar findings concerning task-specific self-beliefs in the L2 English language subject. It was also the female learners who reported a considerably higher amount of worry and emotionality cognitions than the equally achieving male learners (Faber, 2012b). Future research should, therefore, scrutinize the developmental influences which contribute to the females' stronger vulnerability to internal distress ( Taken altogether, the findings considerably differed across both the L1 and the L2 language subject.…”
Section: Discussionmentioning
confidence: 94%
“…Only few studies had already investigated foreign language attributions with respect to specific language outcomes -for example, in reading, speaking, and listening comprehension (Demir, 2017;Gobel & Mori, 2007;Graham, 2006;Lian, 2012;Yilmaz, 2012). However, following empirical findings on learners' self-concepts (Arens & Jansen, 2016;Faber, 2012b;Holder, 2005;Lau, Yeung, Jin, & Low, 1999), further research in the field should more intensely explore task-specific attributions,and also scrutinize relevant instruments' validity, in order to gain more differentiated access to learners' beliefs to control their outcomes in foreign language vocabulary, listening, reading, writing, or grammar.…”
Section: Current Research Gapsmentioning
confidence: 99%